Clinical characteristics and outcomes of patients with TSH-secreting pituitary adenoma and Graves’ disease - a case report and systematic review - Adeel Ahmad Khan (14152953) (2024)
Background Coexistence of TSH-secreting pituitary adenoma (TSHoma) and Graves’ disease (GD) is rare and complicates the management decision. Methods We present a case of the co-existence of TSHoma and GD. In addition, we systematically searched articles describing TSHoma and GD in the same patient published until 20th March 2023, using Pubmed, Scopus and Embase. Case presentation A 46-year-old man presented with symptoms of thyrotoxicosis. His thyroid function tests showed serum TSH 3.35 (reference range 0.3–4.2) mIU/L, FT3 19.7 (3.7–6.4) pmol/L, and FT4 68.9 (11-23.3) pmol/L. The serum TSH receptor antibody was 11.5 mIU/L (positive at ≥ 1.75 mIU/L). Pituitary magnetic resonance imaging showed macroadenoma compressing the optic chiasm. The patient underwent trans-sphenoidal resection of pituitary adenoma. Postoperatively, he remained on maintenance carbimazole and octreotide. Results Fourteen articles comprising 15 patients were identified from the systemic search. A total of 16 patients (including the current case) were included in the systematic review. The mean (± SD) age at diagnosis was 41 ± 13.6 years. The majority were females (75%). The median (IQR) TSH was 1.95 (0.12–5.5) mIU/L, the median (IQR) free T3 was 11.7 (7.6–19.7) pmol/L and the median (IQR) free T4 level was 47.6 (33.3–64.4) pmol/L. Ten (76.9%) patients had positive TSH receptor antibody levels. 84.6% had pituitary macroadenoma. Pituitary surgery was performed in 12 (75%) patients. At the last follow-up, 4 (25%) patients had complete resolution of symptoms after pituitary surgery, 3 (18.7%) were on maintenance treatment with thionamides for GD, 1 (6.25%) on beta-blockers and 1 (6.25%) on somatostatin analog. Conclusion TSHoma and GD can co-exist, and it is essential to identify this rare association as it can significantly impact treatment strategies. Other Information Published in: Thyroid Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s13044-023-00184-2